Loan loss provisions and return predictability: a dynamic perspective - Gao, Phoebe (2022)
This paper examines the impact of loan loss provisions (LLPs) on return predictability during 1994–2017. We find that on average, LLPs are negatively associated with one year ahead stock returns. This effect is particularly significant during the global financial crisis but much weaker during the Basel II and III periods. Consistent with these findings, a long–short trading strategy based on LLPs generates positive abnormal returns during the Basel II and III periods but negative abnormal returns during the financial crisis. Cross-sectional tests show that this effect is more pronounced among banks with greater information asymmetry. Decomposition of LLPs suggests that these findings are driven mainly by nondiscretionary LLPs. Overall, our results suggest that the relationship between LLPs and future stock returns is not linear but contingent on bank regulations and macroeconomic conditions.